2017
DOI: 10.1007/s11192-017-2242-0
|View full text |Cite
|
Sign up to set email alerts
|

Post retraction citations in context: a case study

Abstract: This study examines the nature of citations to articles that were retracted in 2014. Out of 987 retracted articles found in ScienceDirect, an Elsevier full text database, we selected all articles that received more than 10 citations between January 2015 and March 2016. Since the retraction year was known for only about 83% of the retracted articles, we chose to concentrate on recent citations, that for certain appeared after the cited paper was retracted. Overall, we analyzed 238 citing documents and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 31 publications
2
121
1
2
Order By: Relevance
“…Indeed, according to Neale, Dailey, and Abrams (), just less than 5% of citations to retracted articles show no awareness of the retraction notice or related misconduct – a small but still worrying percentage. Additional analyses have also confirmed the rise in citations of retracted articles, regardless of whether there are clear retraction notices and the reason for retraction, such as in cases of ethical misconduct, data fabrication, and false reports (Bar‐Ilan & Halevi, ; Korpela, ; Madlock‐Brown & Eichmann, ; Redman, Yarandi, & Merz, ). What is equally troubling are the findings that there are positive correlations between self‐citations and retraction citations (Madlock‐Brown & Eichmann, ), as well as between pre‐retraction citations and post‐retraction citations (Cokol et al ., ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Indeed, according to Neale, Dailey, and Abrams (), just less than 5% of citations to retracted articles show no awareness of the retraction notice or related misconduct – a small but still worrying percentage. Additional analyses have also confirmed the rise in citations of retracted articles, regardless of whether there are clear retraction notices and the reason for retraction, such as in cases of ethical misconduct, data fabrication, and false reports (Bar‐Ilan & Halevi, ; Korpela, ; Madlock‐Brown & Eichmann, ; Redman, Yarandi, & Merz, ). What is equally troubling are the findings that there are positive correlations between self‐citations and retraction citations (Madlock‐Brown & Eichmann, ), as well as between pre‐retraction citations and post‐retraction citations (Cokol et al ., ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Ego‐network analysis shows decreasing trends in citations post‐retraction (Bornemann‐Cimenti et al, ), but also that these citations still recognized AR “positively” (Bar‐Ilan & Halevi, ) as legitimate work. We also found that citations post‐retraction came from articles affiliated with a different country than the AR .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the continued circulation of retracted articles poses significant risks to the integrity of scientific research as honest and reliable works. (Bar-Ilan & Halevi, 2017;Da Silva & Bornemann-Cimenti, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, papers continue to be cited after retraction, sometimes at a higher rate than before retraction (Bar‐Ilan & Halevi, ; Da Silva & Bornemann‐Cimenti, ; Dong, Loh, & Mondry, ). Even fraudulent papers continue to accrue citations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that post‐retraction citation is mostly positive, and rarely signals the retraction. For instance, bibliographies almost never indicated the retractions in Bar‐Ilan & Halevi's study of 238 post‐retraction citations to 15 papers across disciplines, and only 12 (5%) of these 238 post‐retraction citations were negative [Bar‐Ilan & Halevi, ].…”
Section: Introductionmentioning
confidence: 99%